Gamma knife radiosurgery for trigeminal neuralgia: first case series from Latin America - Constanzo, Felipe; Silva, Rodrigo Souza da; de Almeida, Daniel Benzecry; Ferragut, Maria Alice; Coelho, Mauricio, Neto; Toledo, Hugo Veroneze; Ramina, Ricardo (Arquivos de Neuro-Psiquiatria, 2019)
Gamma Knife® radiosurgery (GKRS) for trigeminal neuralgia is an effective treatment with at least a 50% reduction of pain in 75-95% of patients.Objective: To present the first series of patients treated for trigeminal neuralgia using GKRS in Latin America.Methods: Retrospective analysis. Analysis consisted of time to improvement of symptoms, best Barrow Neurological Institute scale (BNI) score after procedure, time without pain, time to recurrence and post-procedural hypoesthesia.Results: Nineteen cases of classical trigeminal neuralgia were analyzed and three cases of symptomatic trigeminal neuralgia were described. Mean time from symptom onset to radiosurgery was 99.6 months, and 78.9% of patients had undergone invasive procedures before treatment. Patients were followed for a mean of 21.7 months. BNI I was achieved in 36.8%, IIIa in 21.1%, IIIb in 21.1%, IV in 5.3% and V in 15.7%. New hypoesthesia developed in 12.1% patients, which was associated with achieving BNI I after the procedure (p < 0.05). Time from diagnosis to GKRS was higher in patients who failed to achieve BNI I (143 vs. 76 months). The distance from the root entry zone in patients who achieved BNI I was greater than patients who did not (1.94 vs. 1.14 mm). Mean distance from the root entry zone in patients with new hypoesthesia was 2.85 mm vs. 1.06 mm (p = 0.06).Conclusion: Clinical response to GKRS is related to the time between diagnosis and procedure, thus its indication should be considered early in the management of these patients.
Keywords: Trigeminal neuralgia; radiosurgery; neuropathic pain